140 Paediatric injuries resulting from television/tv trolley and other furniture and appliance tip-overs seen in an urban emergency department in karachi, pakistan. (19th September 2017) - Naeem, Rubaba; Ferguson, Rennie; Quddusi, Ayesha; Awan, Safia; Khan, Uzma
Abstract : Background: Significant numbers of childhood deaths are occurring due to trauma with a high percentage of injuries happening within the home environment. More than 95% of all injury deaths in children occur in low-income and middle-income countries. We reviewed paediatric (<16 years) injuries caused by being struck by TV/TV trolley/falling objects retrospectively from January 2010 to December 2014. patient medical records were reviewed for patient demographics and event details. Telephone interviews with parents of injured children were also conducted to collect information about the injury scene and other factors that may inform prevention efforts. Results: From 2010–2014, 55 children were seen at DEM-AKUH following TV trolley and other falling object injuries. 55 children, (69%) of the patients were males and (31%) were female. The median age of children was 4.5 years and ranged from 10 months to 15 years. The most common mechanism of injury was falling TV/TV trolley (40%), followed by bricks and other objects. Among those injured by TV/TV trolleys, (71%) were boys and the majority (93%) were <5 years of age. (71.4%) were admitted to intensive care unit. The most common injuries were to the upper limb (18.5%) and head (10.5%). Half of the patients required surgical procedures (50.8) followed by simple dressing (34%), wound debridement (40.9%) and (15.9%) had laceration repair (33.8%). Of these total 55 children, 35 parental interviews has been done till to date. First aid was provided to (89%) injured children at home. Most common location of the incident was living room (43%) followed by bed room (20%). At the time of incident only (28%) children were under supervision while almost all mothers (94%) were housewives. Conclusion: Injuries caused by falling TVs/TV trolleys are an important home safety issue for parents in Pakistan, and findings underscore the need for increased prevention efforts.